Azerbaijan Systematic Country Diagnostic Update - World Bank (Washington, DC, 2022)
The Azerbaijan Systematic Country Diagnostic (SCD) Update 2022 identifies the most critical challenges facing the government in the effort to achieve the country’s national goals and the twin goals of eradicating extreme poverty and promoting shared prosperity. It also identifies policy priorities to address these challenges within a changing economic and geopolitical environment. The SCD is a comprehensive evidence-based analysis founded on the latest data and analyses available. The document benefited from comments and feedback provided by stakeholders in Azerbaijan, including national authorities, the private sector, and civil society. By reflecting voices on the ground, the SCD is intended to support the implementation of the country’s development agenda as outlined in “Azerbaijan 2030: National Priorities for Socio-Economic Development” (Azerbaijan 2030) (President of the Republic of Azerbaijan 2021). The analysis is built on the findings of the first generation Azerbaijan SCD, which was published in 2015, and also updates the analysis to account for recent developments since 2015. The SCD likewise plays a crucial role in providing an analytical basis for the Country Partnership Framework (CPF), a document that will guide the World Bank’s engagement and partnership with the government of Azerbaijan over the next four to six years.